Объяснение:
Выражение вида
Ах^2+ах+с = А(х-х1)(х-х2).
Где х1; х2 ; корни уравнения
Ах^2+ах+с=0
6х^2+7х-5=О
Д=7^2-4*6*(-5)=49+120=169
Х=(-7+-√169)/12=(-7+-13)/12
Х1= -20/12=-5/3;; Х2=6/12=1/2
Данное выражение разложиться следующим образом:
6(х+5/3)(х-1/2)=(3х+5)(2х-1)
Объяснение:
Выражение вида
Ах^2+ах+с = А(х-х1)(х-х2).
Где х1; х2 ; корни уравнения
Ах^2+ах+с=0
6х^2+7х-5=О
Д=7^2-4*6*(-5)=49+120=169
Х=(-7+-√169)/12=(-7+-13)/12
Х1= -20/12=-5/3;; Х2=6/12=1/2
Данное выражение разложиться следующим образом:
6(х+5/3)(х-1/2)=(3х+5)(2х-1)